2009
DOI: 10.1111/j.1365-2893.2008.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of de novo hepatitis C virus infections and absence of nosocomial transmissions of GB virus C in a large cohort of German haemodialysis patients

Abstract: To determine the prevalence and incidence of hepatitis C virus (HCV) infections among haemodialysis patients, a large prospective multicentre trial was conducted in the German Federal State of North Rhine-Westphalia. Sera obtained from the recruited patients in two separate sampling rounds run 1 year apart were analysed for both anti-HCV antibodies and HCV RNA. HCV RNA positive samples were also genotyped by direct sequencing of an HCV core fragment. In the first and second rounds, 150 (5.2%) of 2909 and 114 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
13
0
2
Order By: Relevance
“…While the trak-C assay could not detect core antigen in 10 of 90 HCV RNApositive samples obtained from German hemodialysis centers (38), its Architect counterpart correctly recognized all of these specimens with very low levels of HCV viremia. Therefore, use of the Abbott test might provide at least an interim solution for the yet unresolved issue and the still ongoing discussion in the dialysis community of the need for and advantage of supplemental HCV RNA testing of anti-HCV-negative patients on maintenance hemodialysis (3,7,9,16,40). Similar considerations could apply to other settings, including transplantation medicine, in which the availability of a sensitive immunoassay for HCV core antigen determination should also represent a valuable diagnostic benefit for the immediate resolution of peculiar serological constellations which are particularly problematic in the course of decision making (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the trak-C assay could not detect core antigen in 10 of 90 HCV RNApositive samples obtained from German hemodialysis centers (38), its Architect counterpart correctly recognized all of these specimens with very low levels of HCV viremia. Therefore, use of the Abbott test might provide at least an interim solution for the yet unresolved issue and the still ongoing discussion in the dialysis community of the need for and advantage of supplemental HCV RNA testing of anti-HCV-negative patients on maintenance hemodialysis (3,7,9,16,40). Similar considerations could apply to other settings, including transplantation medicine, in which the availability of a sensitive immunoassay for HCV core antigen determination should also represent a valuable diagnostic benefit for the immediate resolution of peculiar serological constellations which are particularly problematic in the course of decision making (20).…”
Section: Discussionmentioning
confidence: 99%
“…These materials were available from a former study performed by our group (40) and allowed comparison of the HCV core antigen determinations by the Architect assay with those previously determined by the trak-C test (Johnson & Johnson, Ortho Clinical Diagnostics, Rochester, NY).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated prevalence of HCV infection (i.e., anti-HCV antibody positive) in dialysis patients was approximately 8% in the USA [1], 5% in Germany [2] and 10% in Japan [3]. Standardized prevalence rates for anti-HCV antibody were 13-fold higher in men and 9-fold higher in women when compared with the population-based controls [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there are many studies available in the literature showing that isolation of HCV-positive patients decreases HCV seroconversion [11,12,13,14,15,16,17,18,19,20]. Brief findings of these studies are shown in table 1.…”
Section: Evidence That Isolation Decreases Hcv Seroconversionmentioning
confidence: 93%